Las mujeres de Hispanoamérica época colonial ([Colecciónes MAPFRE 1492 / 7], 1992)
"Carefully structured synthesis based on extensive study of published monographs plus some archival sources examines the role of women in preconquest societies and the conquest itself. Uses regional approach emphasizing New Spain and Peru. Thoroughly footnoted"--Handbook of Latin American Studies, v. 58.. - http://www.loc.gov/hlas/